2012
DOI: 10.1016/j.dhjo.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of total serum cholesterol with functional outcome following home care rehabilitation in Italian patients with stroke

Abstract: Elevated TC seems to be associated with better functional outcomes in patients with first-time stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Besides being implemented to screen for cognitive dysfunction, it has also been widely used as a general measure of cognitive abilities, especially in the prediction of memory performance (Stump, Callahan, & Hendrie, 2001; Welch & West, 1999). The Italian version of this instrument has been shown to detect rates of cognitive impairment comparable to those reported in population-based studies conducted in other countries (e.g., Salemi et al, 2002); moreover, findings have confirmed its predictive validity with respect to different outcomes among Italian elderly people (e.g., Bo et al, 2003; Cataldo, Calcara, Caputo, & Mammina, 2012). The instrument was administered only to the grandparents to control for their mental health.…”
Section: Methodssupporting
confidence: 70%
“…Besides being implemented to screen for cognitive dysfunction, it has also been widely used as a general measure of cognitive abilities, especially in the prediction of memory performance (Stump, Callahan, & Hendrie, 2001; Welch & West, 1999). The Italian version of this instrument has been shown to detect rates of cognitive impairment comparable to those reported in population-based studies conducted in other countries (e.g., Salemi et al, 2002); moreover, findings have confirmed its predictive validity with respect to different outcomes among Italian elderly people (e.g., Bo et al, 2003; Cataldo, Calcara, Caputo, & Mammina, 2012). The instrument was administered only to the grandparents to control for their mental health.…”
Section: Methodssupporting
confidence: 70%
“…Several works have been published in recent years studying the role of blood levels of total cholesterol in the functional outcomes of IS patients. Some authors have found evidence that high levels of total cholesterol are associated with better functional outcomes [89][90][91] . By contrast, despite several prospective studies in recent years, the role of triglycerides in the risk of IS and HS remains controversial [92] .…”
Section: Metabolites As Prognostic Biomarkersmentioning
confidence: 99%